The performance study of two genetic algorithm approaches for VLSI Macro-Cell layout area optimization - Hasliza, A. Rahim@Samsuddin; Rahman, A. A A; R. Badlishah, Ahmad; Wan Nur Suryani Firuz, Wan Ariffin; Muhammad Imran, Ahmad (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org